Trace Element Content in the Soils of the Forest-Steppe of Western Siberia - Goman , Natalia; Bobrenko, Igor; Matveychik, Oleg; Popova, Valentina; Bobrenko, Elena (KnE Life Sciences, 2021)
This research is based on local monitoring in 1994-2018 on reference plots of agricultural lands and materials of a large-scale agrochemical survey. The research examined the soils of the forest-steppe zone of the Omsk Region: ordinary chernozem low-power low-humus heavy loamy soil; meadow-chernozem medium-thick medium-humus heavy loamy soil; and solonetz meadow chernozemic deep low humus clay soil. It was found that almost the entire surveyed area of arable land in the forest-steppe zone of the Omsk Irtysh Land (98.1 %) had low mobile zinc availability with an average level of 0.85 mg/kg. 41.1% of arable land had low mobile manganese availability, 41.3% had medium and 17.6% had high availability; the weighted average was 13.0 mg/kg. Most of the arable land was characterized by a low degree of mobile copper content security (81.2%), while 18.3% of the land had soil with an average content, and only 0.5% of the land had high mobile copper content. The average concentration was 20.0 mg/kg. The soil levels of mobile molybdenum availability wereas follows: 71.6% of land had medium availability, 26.5% had high, and only 1.9% had low; the weighted average concentration was 0.20 mg/kg. All soils had a high degree of mobile forms of boron, while the weighted average was 2.69 mg/kg of soil. 67.8% of the area had low mobile cobalt availability, 31.6% had average availability, and 0.5 % had high availability, with an average concentration of 0.16 mg/kg in the zone. The reference plots did not differ in terms of their content of mobile zinc, copper, and cobalt, ordinary chernozems, meadow chernozem soils, and deep solonetz. Movable connections of molybdenum, manganese, and boron in ordinary chernozem were lower than in meadow chernozem soil, and the maximum ones were observed in solonetz meadow chernozemic deep. Keywords: trace elements, content, soil, survey, dynamics, Omsk region